Dealing with discontinuous innovation: the European experience. (30th April 2008) - Bessant, John
Recent research has drawn attention to problems with innovation management under conditions of discontinuity. For example, at certain times, the close interaction with players within the value network may act as a filter which blocks firms seeing the salience of new signals about emerging, but very different potential, technical or market trajectories. There is also the well-known issue of 'not invented here' suggesting that under conditions in which significant shifts occur in the technological trajectory existing incumbents often fail to capitalise or even to adopt. The problem is not simply one of missing important signals about emerging shifts in innovation trajectories in the environment. In a number of cases the information was available to the enterprise but its decision making and resource allocation processes failed to deal adequately with the new information. These and other experiences suggest that whilst firms can learn capabilities around what might be termed 'steady state' innovation conditions they need to extend these capabilities to deal with the uncertainties arising from discontinuous shifts in their technological, market or regulatory environments. This paper discusses some of the challenges around building such capability and presents some case study-based illustrations of experiments in progress.